Circularly Polarized Fluorescence Resonance Energy Transfer (C‐FRET) for Efficient Chirality Transmission within an Intermolecular System. (7th October 2021) - Wu, Yue; Yan, Chenxu; Li, Xin‐Shun; You, Li Hong; Yu, Zhen‐Qiang; Wu, Xiaofeng; Zheng, Zhigang; Liu, Guofeng; Guo, Zhiqian; Tian, He; Zhu, Wei‐Hong
Abstract: The occurrence and transmission of chirality is a fascinating characteristic of nature. However, the intermolecular transmission efficiency of circularly polarized luminescence (CPL) remains challenging due to poor through‐space energy transfer. We report a unique CPL transmission from inducing the achiral acceptor to emit CPL within a specific liquid crystal (LC)‐based intermolecular system through a circularly polarized fluorescence resonance energy transfer ( C ‐FRET), wherein the luminescent cholesteric LC is employed as the chirality donor, and rationally designed achiral long‐wavelength aggregation‐induced emission (AIE) fluorophore acts as the well‐assembled acceptor. In contrast to photon‐release‐and‐absorption, the chirality transmission channel of C ‐FRET is highly dependent upon the energy resonance in the highly intrinsic chiral assembly of cholesteric LC, as verified by deliberately separating the achiral acceptor from the chiral donor to keep it far beyond the resonance distance. This C ‐FRET mode provides a de novo strategy concept for high‐level information processing for applications such as high‐density data storage, combinatorial logic calculation, and multilevel data encryption and decryption. Abstract : Circularly polarized luminescence (CPL) transmission is a critical challenge in chiroptical research but there are two questions on CPL transmission. How to transfer CPL within intermolecular systems? And can achiral emitters emit CPL? We find the CPL transmission is critically dependent on the resonance transfer, which was attributed to unique circularly polarized fluorescence resonance energy transfer ( C ‐FRET).